"Change my selfie": Relationships between self‐objectification and selfie‐behavior in young Italian women. Issue 9 (20th July 2020) - Caso, Daniela; Schettino, Giovanni; Fabbricatore, Rosa; Conner, Mark
Abstract: Self‐objectification is a pervasive phenomenon, related to specific socio‐cultural context, that can lead to many psychological and interpersonal consequences. With the present study, we investigated the correlates of self‐objectification in young Italian women analyzing both its traditional antecedents and its consequences for self‐presentation on social network sites (SNS). A total of 676 Italian university female students completed a self‐reported questionnaire on self‐objectification, internalization of a thin‐ideal and related influences, internalized sexism, self‐esteem, SNS use, selfie‐posting on SNS and selfies' manipulation. Results indicated that media and peers, but not family pressures, were positively associated with thin‐ideal internalization, which, in turn, was positively associated with self‐objectification. Moreover, both sexism and self‐esteem were significantly associated with self‐objectification. Regarding self‐objectification consequences for SNS usage, results revealed that self‐objectification was positively associated with time spent on SNS, frequency of selfie‐posting and selfie‐editing. It was concluded that objectification theory can be extended into the context of image‐related behaviors on SNS. Results suggest that young women with low self‐esteem, traditional attitudes toward gender roles and high levels of internalization of thin‐ideal may report high levels of self‐objectification which, in turn, may be related to specific self‐promotion behaviors on social media. The limitations of the present study, particularly in terms of sampling and implications for future research on selfie‐behavior are discussed.